Design and Analysis of mmWave Patch Antenna for 5G and 6G Applications (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents the design, simulation, and analysis of a compact millimeter-wave (mmWave) patch antenna optimized for multi-band operation targeting 5G and emerging 6G communication systems. The proposed antenna operates efficiently at 24.5 GHz, 26.63 GHz, 29.375 GHz, and 31.35 GHz, offering high gain, low sidelobe levels, and effective impedance matching. The antenna structure integrates a circular patch with an embedded slotted H-shaped element, enhancing multi-resonant behavior while maintaining a compact form factor. Precise geometrical tuning of the slots, feedline, and parasitic elements enables multi-band resonance and directional radiation characteristics. Simulations were conducted using CST Studio Suite®, analyzing S-parameters, VSWR, and radiation patterns. The antenna exhibits return loss values below –10 dB across all operational bands and achieves a peak gain of 6.38 dBi at 31.35 GHz. The corresponding VSWR remains under 1.5 at key frequencies, indicating efficient power transfer. Far-field analysis reveals focused radiation patterns with low sidelobe levels, suitable for high-frequency beam-steering applications. Additionally, 3D gain plots demonstrate directional behavior with minimal losses, confirmed by high radiation and total efficiency values. The design’s performance suggests strong potential for deployment in advanced mmWave systems, including 5G/6G base stations, satellite links, and precision-guided communication systems.
Keywords: 5G; 6G; mm wave Antenna; CST Studio; Millimeter-wave; High Efficiency